Effectiveness of Monte Carlo Simulations of the S&P 500 Index before and after the Outbreak of the SARS-COV-2 Pandemic - Nawrocki, Piotr (Efektywność symulacji Monte Carlo indeksu S&P 500 przed ogłoszeniem i po ogłoszeniu pandemii SARS-COV-2)
Risk analysis is an integral part of studying the behavior of financial markets. Crises and emergencies challenge analysts trying to predict the value of stock indices by questioning their assumptions. One such event was the coronavirus pandemic, which undoubtedly affected our economy. The purpose of this study was to examine the impact of the COVID-19 pandemic on the US market and to assess the change in effectiveness of the Monte Carlo method due to the pandemic. The study was realized with 12 MC simulations of daily S&P 500 index prices using historical data from 11.03.2015 to 11.03.2021. The negative impact of the pandemic on the accuracy of MC simulations was observed, lowering the confidence of the results. Changes in sensitivity depending on the chosen time period were also detected. The results may prompt consideration of modifying MC simulations during instability and provide information indicating the use of shorter time series to improve simulation efficiency during crises.
Financial Sciences. Nauki o Finansach, 2023, vol. 28, no. 1, s. 1-16
Keywords: Monte Carlo methods; Black-Scholes model; index simulation; COVID-19 pandemic; metoda Monte Carlo; model Blacka-Scholesa; symulacja indeksu; pandemia COVID-19